An Evaluation of The Outcome of Stepwise Treatment of Subfertility in Women with Polycystic Ovary Syndrome (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women accounting for approximately 80% of all cases of anovulatory infertility. This prospective study evaluated the fertility outcomes of a stepwise conservative management protocol for women with polycystic ovary syndrome (PCOS) and anovulatory infertility. Methods: A total of 117 eligible women were initially enrolled, with 104 completing the 2.5-year treatment and follow-up with 13 patients completely lost to follow up. The protocol followed a progressive approach, beginning with lifestyle modifications and advancing to pharmacological ovulation induction with clomiphene citrate and letrozole. In the 1st-line of treatment, there were three steps. The Step-I, 1st-line of treatment consisted of Life-style modification (dietary modification and exercise) with or without Metformin (850 mg in twice daily doses). The Step-II, 1st-line of treatment comprised of Clomiphen citrate, started with 50 mg/day, increased by 50 mg in each cycle up to 250 mg daily for a maximum of 6 cycles. The Step-III, 1st-line of treatment was done with Letrozole (started with 2.5 mg daily increased by 2.5 mg in each cycle up to 6 cycles). In the 2nd line of treatment there were two steps. The Step-I, 2nd-line of treatment was given with combination of clomiphene citrate + FSH + hCG. The Step-II, 2nd-line of treatment was done with Letrozole + FSH started at 37.5–75 IU/day (maintained for 1 week and then increased every week until follicular growth) + hCG. While the main outcome variable was live-birth, occurrence of ovulation, clinical pregnancy and miscarriage were the accessory outcome variables.Results: The study found a clinical pregnancy rate of 82.7% and a cumulative live birth rate of 63.5% (66/104). Lifestyle modifications alone were effective for a portion of the cohort, leading to a 19.2% clinical pregnancy rate. Subsequent treatment with clomiphene citrate and letrozole further increased pregnancy rates, with letrozole demonstrating a higher live birth rate (31.25%) compared to clomiphene citrate (28.1%). An overall miscarriage rate of 23.3% was observed.Conclusion: These findings suggest that a stepwise conservative approach is a highly effective management strategy for anovulatory infertility in this specific patient population, and they support the use of letrozole as a first-line pharmacological agent. The study highlights the feasibility and success of this treatment paradigm in a regional context and provides a foundation for future, larger-scale research.Ibrahim Card Med J 2024; 14 (2): 17-25